VNS in drug resistant epilepsy: preliminary report on a small group of patients - Iero Luisa; Cecconi Ilaria; Brunetto Daniela; Colonnelli Maria; Gentile Valentina; Franzoni Emilio; Moscano Filomena C; Cordelli Duccio M; Marchiani Valentina (BMC, 2010)
Abstract Background In 1997 Vagus Nerve Stimulation (VNS) received approval from the US Food and Drug Administration (FDA) as an adjunctive therapy in the treatment of medically intractable partial epilepsy in people aged 12 years and older who are ineligible for resective epilepsy surgery. Although the exact mechanisms of action are unknown, the use of VNS with children has increased, including those younger than 12 years of age, or those with generalized epilepsy. Methods We describe the outcome for the first group of nine patients, aged 8-28 years, who had pharmaco-resistant epilepsy and were treated with VNS. During the follow up, we gradually and slowly increased the parameters of the stimulation in order to assess the efficacy of VNS even at parameters which would usually be considered "non-therapeutic", along with possible side effects and changes in quality of life. Results At the last follow, up 1 patient was "seizures free", 3 were "very good responders", 3 were "good responders" and 2 were "non responders". We obtained an initial seizure reduction with low stimulation parameters, the highest current reached being 2.00 mA. This observation supports the possibility that, for younger patients, lower stimulation intensities than those commonly used in clinical practice for adults can be therapeutic. We also wanted to underline the reduction in seizure frequency (~91,7%) and the reduction in seizure duration (> 50%) in the patients affected by drug-resistant absence epilepsy. Adverse effects were mild, tolerable and, in most of cases, easily resolved by adjusting the stimulation parameters. Hoarseness of voice was the most frequent side effect. The improvements in the quality of life are relevant and seem to be independent of the VNS effect in controlling seizures. Conclusions Our small experience seems to confirm the efficacy and safety of VNS in drug resistant partial and generalized epilepsy in developing age groups.